31PTepotinib inhibits the epithelial-mesenchymal transition and tumour growth of gastric cancers via decreasing MUC5B, MMP7, and COX2. (7th November 2019) - Zang, D Y; Sohn, S-H; Sul, H J; Kim, B; Choi, B Y; Kim, H S
Abstract: Background: Aberrant expression of mucins can promote the epithelial-mesenchymal transition (EMT), which leads to enhanced tumorigenesis. Carcinogenesis-related pathways involving c-MET and β-catenin involve mucins. Among the mucins, MUC5AC and MUC6 are characteristic for stomach mucins. This study characterized expressions of MET, MUC5AC, MUC5B, and MUC6 EMT signaling in human gastric cancer (GC) cell lines, and further characterized the differential susceptibility of these cell lines to tepotinib. Methods: We assessed the antitumor activity of tepotinib in GC cell lines. The effect of tepotinib on cell viability (IC50 ), apoptotic cell death, the EMT, and c-MET and β-catenin signaling were evaluated by MTS, flow cytometry, western blotting, and qRT-PCR. Antitumor efficacy was assessed in MKN45 xenograft mice. Results: Tepotinib treatment showed dose-dependent growth inhibition of c-MET-amplified SNU620, MKN45, and KATO III cells with concomitant induction of apoptosis, but tepotinib treatment did not have an effect on c-MET-reduced MKN28 and AGS cells. Tepotinib treatment also significantly reduced expressions of phosphor-c-MET, total c-MET, phosphor-ERK, total ERK, beta-catenin, and c-MYC protein in SNU620 and MKN45 cells. In contrast, this drug was only slightly active against KATO III cells. Notably, tepotinib significantly reduced the expressions of EMT promotion genes such as MMP7, COX-2, WNT1, MUC5B, and c-MYC in c-MET-expressed GC cells, and increased expressions of EMT suppression genes such as MUC5AC, MUC6, GSK3β, and ECAD. In a murine xenograft model, tumor volumes were significantly reduced in the tepotinib-treated group, when administered by daily oral gavage at a dose of 10 mg/kg/day. Histologically, tepotinib induced more necrosis than in the control group. Conclusions: These results are consistent with clinical evaluations of tepotinib in c-MET and MUC5B-expressed GCs. Editorial acknowledgement: National R&D Program for Cancer Control, Ministry of Health and Welfare (HA17C0054), the National Research Foundation of Korea grant funded by the Korean Ministry of Science and ICT (NRF-2017R1A2B4005055), the Ministry of Food and Drug Safety (awarded in 2018, 18183MFDS491) of Korea, the Hallym University Medical Center Research Fund, and the Hallym University Internal Translational Research Fund (No. HURF-2015-38). Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.